Sodium Storage: Controlled SnO2 Crystallinity Effectively Dominating Sodium Storage Performance (Adv. Energy Mater. 10/2016). Issue 10 (May 2016) - Fan, Linlin; Li, Xifei; Yan, Bo; Feng, Jianmin; Xiong, Dongbin; Li, Dejun; Gu, Lin; Wen, Yuren; Lawes, Stephen; Sun, Xueliang
Abstract : The exploration of sodium ion batteries (SIBs) is a profound challenge due to the rich sodium abundance and limited supply of lithium on earth. Meanwhile, as more demand emerges for electrical vehicles (EVs), SIBs have tremendous applications. In article number 1502057, Xifei Li, Lin Gu, and Xueliang Sun employ amorphous and crystalline nanocomposites as electrode materials of the two distinct batteries on the cover, which can sustain the operation of EVs.